1998
DOI: 10.1007/s005920050102
|View full text |Cite
|
Sign up to set email alerts
|

Family history and risk of insulin-dependent diabetes mellitus: a population-based case-control study

Abstract: Insulin-dependent diabetes mellitus (type 1) is a common chronic disease of childhood occurring throughout the world. In the literature, its most important determinants include genetic, environmental and familial factors. We evaluated family history as a determinant of the risk of type 1 diabetes mellitus with a population-based case-control study. Information about type 1 patients was taken from the dedicated register of the Abruzzo Region; the register has been collecting incident cases in the age group 0-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 16 publications
4
26
5
Order By: Relevance
“…We estimated an OR of about 13, even higher than the risk among the under 5s in a Swedish [11]. A case of type 2 diabetes in the family was not associated with an increased type 1 diabetes risk in our study, in line with some [52] but not all investigations [11,21]. Epidemiological evidence on the association between socio-economic status and type 1 diabetes risk in children is fairly conflicting, possibly owing to different study designs or differing methods for assessing social status.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We estimated an OR of about 13, even higher than the risk among the under 5s in a Swedish [11]. A case of type 2 diabetes in the family was not associated with an increased type 1 diabetes risk in our study, in line with some [52] but not all investigations [11,21]. Epidemiological evidence on the association between socio-economic status and type 1 diabetes risk in children is fairly conflicting, possibly owing to different study designs or differing methods for assessing social status.…”
Section: Discussionsupporting
confidence: 85%
“…A positive family history of type 1 diabetes has consistently been reported to raise type 1 diabetes risk among relatives [2,9,11,20,21,23,51,52]. But reported ORs varied considerably, partly due to different age groups investigated or different definitions of familial type 1 diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…In the literature increasing maternal and paternal age have been found both to increase the risk [2][3][4], while in other studies [5,6] no association was found, in addition being first born is found both to increase [4,7] and decrease the risk [2]. By contrast a family history of diabetes is consistently found to increase the risk [8,9]. Besides different intrauterine risk factors affect the risk of childhood diabetes; prenatal growth was a risk factor in the studies by Dahlquist et al [2] and Stene et al [10] while others dispute this [11][12][13][14], decreasing gestational age was associated with an increased risk in a Danish study [14] while other authors have not found an association [5,10,11,15].…”
Section: Introductionmentioning
confidence: 79%
“…This phenomenon can be explained by genetic predisposition to diabetes and hypertension [30,31,32,33,34], the common causes of ESRD and CKD, as well as the predominantly genetic etiology of other causes of renal failure (e.g., polycystic kidney disease, Alport’s syndrome). Potential confounding of evidence for a familial component by the presence of hypertension, but not diabetes, has been demonstrated in the past [11].…”
Section: Discussionmentioning
confidence: 99%